INVESTIGATION ON THE AFLATOXIN CONTAMINATION OF MILK IN TEHRAN AREA - G.Karim; V.Parvaneh; J.Kordi (Tehran University of Medical Sciences, 1982)
In this survey Aflatoxin contamination of fifty two samples of raw milk and nine samples of commercial milk were determined by T.L.C. Method. The results showed that 92.31% of the samples of raw milk and all the samples of commercial milk were contaminated by Aflatoxin M1 and M2. None of the samples contained Alatoxin B1, B2, G1 and G2. The maximum amounts of 23/. g/lit and 20.1 g/lit were found in raw and commercial milk respectively. Recommendation to prevent Aflatoxin contamination in raw milk and necessity for preparation the standards for milk, milk products and foods were suggested in this paper.